DESAIN SIRKUIT BATTERY MANAGEMENT SYSTEM (BMS) ALTERNATIF DENGAN FUNGSI OVER-DISCHARGE PROTECTION DAN OVERCHARGE PROTECTION - Agus, Agus Nurcahyo; Alimi , Sabri (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2024)
The increasing demand for safe and efficient batteries for renewable energy storage calls for the development of reliable and innovative Battery Management Systems (BMS). One of the main challenges in designing a BMS is creating a system that is not only effective but also easy to build using widely available components. This research aims to produce a BMS circuit design that can contribute to the development of BMS technology in society, with a focus on overcharge and overdischarge protection functions. In the proposed design, the discharge control switch will interrupt the power flow from the battery to the load when any battery cell experiences overdischarge. Similarly, the charge control switch will disconnect the charging power from the charger to the battery when a cell experiences overcharge, and the charging will resume if all battery cells are within safe conditions. This design aims to safety in battery usage across various applications, while providing an easily implementable BMS solution that can be widely adopted by society.